Analysis of Infrastructure Conditions Following the Flash Flood (Galodo) Disaster in Lima Kaum Vilage, Lima Kaum District, Tanah Datar Regency - Elga Mayu Hendra; Erna Juita; Elvi Zuriyani; Dasrizal Dasrizal (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2025)
The high susceptibility of West Sumatra to hydrometeorological disasters, particularly galodo (flash floods), necessitates comprehensive assessments of post-disaster infrastructure conditions to support effective recovery and disaster risk reduction. This study aims to evaluate the extent of infrastructure damage caused by the galodo flash flood that struck Nagari Lima Kaum, Lima Kaum District, Tanah Datar Regency, in May 2024. A quantitative research approach was employed using a survey design. The study population comprised households located in the affected areas, with 200 respondents selected from 797 households through proportional random sampling across four villages (jorong): Dusun Tuo, Balai Labuah Atas, Balai Labuah Bawah, and Piliang. Primary data were collected through structured questionnaires and field observations, while secondary data were obtained from the Nagari Lima Kaum Office and the Regional Disaster Management Agency (BPBD) of Tanah Datar Regency. The level of infrastructure damage was analyzed using a Likert-scale-based assessment. The findings reveal that the overall infrastructure damage was classified as high, with a damage index of 80.56%. The most severe impacts were observed in residential buildings and public infrastructure, particularly bridges and places of worship, whereas educational and healthcare facilities experienced relatively lower levels of damage. These findings underscore the urgent need to strengthen resilient infrastructure, improve post-disaster recovery strategies, and integrate disaster risk reduction measures into regional development planning in flash-flood-prone areas.